2015
DOI: 10.1002/lary.25589
|View full text |Cite
|
Sign up to set email alerts
|

Epiglottis collapse in adult obstructive sleep apnea: A systematic review

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 46 publications
2
96
0
3
Order By: Relevance
“…Indeed, available evidence indicates that identifying the epiglottic collapse has important implications for OSA management[9, 32]. The method developed in this study can be used to test whether epiglottic collapse, assessed using this approach, predicts responses to therapy, including failure of oral appliances[9], surgery[33], increased occurrence of collapse on CPAP[10, 11, 32], and effectiveness of positional therapy[17, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, available evidence indicates that identifying the epiglottic collapse has important implications for OSA management[9, 32]. The method developed in this study can be used to test whether epiglottic collapse, assessed using this approach, predicts responses to therapy, including failure of oral appliances[9], surgery[33], increased occurrence of collapse on CPAP[10, 11, 32], and effectiveness of positional therapy[17, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The method developed in this study can be used to test whether epiglottic collapse, assessed using this approach, predicts responses to therapy, including failure of oral appliances[9], surgery[33], increased occurrence of collapse on CPAP[10, 11, 32], and effectiveness of positional therapy[17, 32]. In addition, its utility as a screening tool for epiglottis-related surgery can be tested.…”
Section: Discussionmentioning
confidence: 99%
“…19 Before the use of DISE to evaluate upper airway obstruction, the prevalence of epiglottic collapse was estimated to be 12% of OSA patients. However, studies performed during (drug-induced) sleep have demonstrated a much higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the understanding that the nose generally is not considered a site of obstruction during apneic events, since the nose does not move dynamically. The more susceptible areas of collapse include the oropharynx, hypopharynx, soft palate, and epiglottis in OSA patients [21, 33]. …”
Section: Discussionmentioning
confidence: 99%